UPAYA DINAS SOSIAL KOTA PEKANBARU DALAM KETERTIBAN SOSIAL (STUDI MASALAH ANAK JALANAN) TAHUN 2018-2019 - Romando "; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This Study discusses the efforts of the Pekanbaru City Social Service in Social Order (Study Focus of Street Children Social Problems in 2018-2019) whose condition is apprehensive, because their condition is still underage and they shouldn't beg and make a living on the streets. what is the form of coordination between the Pekanbaru City Government in carrying out control and guidance for street children. In this study, the Pekanbaru City Social Service was the executor of the coordination action.The purpose of this study discusses how the coordination of the Pekanbaru City Social Service with the Pekanbaru City Civil Service Police Unit in carrying out control and coaching of street children and the inhibiting factors of the Pekanbaru City Social Service in carrying out policing and fostering street children. This research uses qualitative research methods, with descriptive analysis of the data. In collecting data, researchers used interview techniques and documentation.The results showed that the Pekanbaru City Social Service in carrying out policing and fostering street children who coordinated with the Civil Service Police Unit, Civil Servant Investigators, and related agencies was not optimal, not appropriate and implemented as in perda number 12 of 2008 concerning social order. This is evidenced by the fact that there are still many street children who act and roam the streets and are caused by the lack of seriousness of the local government of Pekanbaru city in controlling and fostering street children. However, there are also inhibiting factors that affect the performance of local governments in controlling and fostering street children, namely lack of budget, inadequate facilities and infrastructure, and environmental factors. Keywords: Social Order, Street Children